치과위생사의 방사선 안전관리 수행도 관련 요인 - 정종윤; Jong Yun Jeong; 한미아; Mi Ah Han; 박종; Jong Park; 류소연; So Yeon Ryu (Han'guk Ch'iwisaeng Hakhoe chi, 2016)
Objectives: The purpose of the study was to investigate the related factors of performance of radiation safety management in dental hygienists. Methods: A self-reported questionnaire was completed by 183 dental hygienists using dental radiography in 110 dental clinics in G area by convenience sampling methods. The questionnaire consisted of general characteristics of the subjects, radiation-related characteristics, and performance and management of radiation safety. Results: Performance score of radiation safety management was 35.71±12.49 in dental hygienists. The performance score of radiation safety management were associated with sex, numbers of dental hygienists, the average numbers of admitted patients per day, the total clinical experience, existence of manual for radiation safety management and perceived need for education of radiation safety management. Conclusions: The performance score was relatively low. The performance score was associated with radiation safety manual and safety equipment. The preparation of radiation protective environment and equipment will improve the performance of radiation safety management in dental hygienists.